Bacterial communities as indicators of soil health under a continuous cropping system. (5th March 2021) - Shi, Guiying; Sun, Hongqiang; Calderón‐Urrea, Alejandro; Li, Mouqiang; Yang, Hongyu; Wang, Wenzhu; Su, Guoli
Abstract: With growing global interest in the improvement of soil quality and the adoption of sustainable land management systems, there is an urgent need to find early indicators to monitor and manage sustainable soil health. Meta‐analyses provide useful information on microbial communities and community‐level molecular characteristics, which can be exploited as 'biomarker' indicators of ecosystem processes for soil health evaluation. Lanzhou lily ( Lilium davidii var. unicolor ) is the only type of sweet edible lily in China, as well as an endemic species with a narrow distribution. Due to its uses as food and in gardening, this lily has an economic value in the Country, particularly in Gansu Province located in the Loess Plateau. This lily is usually cultivated in long‐term continuous monoculture (replanting), resulting in the so‐called consecutive replanting problem (CRP), which is associated with severe soil degradation and significant yield and quality losses. This study was conducted to investigate the bacterial community structure and specific bacterial members related to the lily's CRPs and soil health degradation indicators via next‐generation sequence (NGS) analysis. The bacterial diversity of rhizosphere soil was analyzed by high‐throughput DNA sequencing (Miseq) of samples collected in fields at 0, 3, 6, and 9 replanting years (L0, L3, L6, and L9, respectively). Results showed that long‐term replanting significantly increased soil bacterial abundance and insignificantly changed soil bacterial diversity. However, replanting altered the soil microbial communities where 3–6 years of replanting was a transmission period for change, resulting in a new community structure after 9 years of replanting. Some specific bacterial members were found to be correlated with lily's plant growth, both positively and negatively. Long‐term replanting accumulation of the harbored highly abundant pathogenic bacterial genus Streptomyces and the species Bacillus simplex and depletion of the plant‐beneficial bacteria genera Sphingomonas and Hyphomicrobium are the causes of the lily's CRP under a 0–9 year replanting system. In addition, changes in the soil physiochemical properties contributed to the new structure of bacterial communities, and the phylum Proteobacteria and the genus Sphingomonas could be regarded as potential indicators of sustainable soil management.